Multirod Pumping Approach with Fresnel Lens and Ce:Nd:YAG Media for Enhancing the Solar Laser Efficiency - Almeida, Joana (2024)
CEECIND/09483/2023. © 2024 by the authors. Licensee MDPI, Basel, Switzerland.